HIGH LEVEL OF IL -1 RECEPTOR ANTAGONIST AS A LETHALITY FACTOR IN PATIENTS WITH SURGICAL SEPSIS - V. V. Grebenyuk; G. A. Makarova; N. V. Yusan (Медицинская иммунология)
Absract. The data are presented that concern the levels of IL-1 receptor antagonist (IL-1 Ra) in blood serum of twenty-five patients with severe surgical sepsis. Sixteen patients recovered from the condition, whereas lethal outcome was registered in nine cases. The study was performed by means of immunoassay, using «IFA-Best IL-1 Ra» kits supplied by the Vector-Best firm. Only three patients showed IL-1 Ra contents within normal limits, whereas others exhibited marked increase in IL-1 Ra levels, up to a mean of 2443.656±382.85 pg/ml (normal range, 50 to 1000 pg/ml).